1986
DOI: 10.1021/es00147a011
|View full text |Cite
|
Sign up to set email alerts
|

Depth profiles for hydrocarbons and polycyclic aromatic hydrocarbons in soil beneath waste disposal pits from natural gas production

Abstract: Soil samples were obtained at four depths from 0 to 121 cm below unlined earthen waste pits associated with production, processing, and distribution of natural gas in the San Juan basin of northwest New Mexico. Sample extracts were analyzed by using capillary gas chromatography and gas chromatography/mass spectrometry for polycyclic aromatic hydrocarbons (PAH) to characterize potential for contamination of shallow groundwater. All soils contained complex mixtures of over 60-100 resolved hydrocarbons with carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Water and drilling wastes have, however, not been associated with high atmospheric benzene concentrations in previous studies [ Bloomdahl et al ., ; Bunch et al ., ], although published atmospheric measurements of these waste pits are difficult to locate. Environmental impacts from these waste pits are more likely to be associated with poor water quality [ Eiceman et al ., ; Gross et al ., ]. Also, the transient nature of the benzene source is hard to explain by slow evaporative emissions from drilling flowback of waste mud and water.…”
Section: Discussionmentioning
confidence: 98%
“…Water and drilling wastes have, however, not been associated with high atmospheric benzene concentrations in previous studies [ Bloomdahl et al ., ; Bunch et al ., ], although published atmospheric measurements of these waste pits are difficult to locate. Environmental impacts from these waste pits are more likely to be associated with poor water quality [ Eiceman et al ., ; Gross et al ., ]. Also, the transient nature of the benzene source is hard to explain by slow evaporative emissions from drilling flowback of waste mud and water.…”
Section: Discussionmentioning
confidence: 98%
“…Assuming an intermediate velocity of 30 cm per day, liquid introduced to an unlined pit would travel to the water table in 3.3 days if the initial water table is 1 m below land surface and soil is saturated. Actually, these calculations and experimental results were not surprising based on a prior study of core samples from a similar pit to depths of nearly 2 m. 16 In that study, evidence for extensive mobility for all compounds was found. Moreover, sandy soils have been found to have limited retardation for aromatic and halogenated aromatic hydrocarbons in laboratory study" and in an actual environmental aquifer.…”
Section: Environmental Assessment and Summarymentioning
confidence: 53%
“…Recently, hydrocarbons and PAH were found in soil below waste pits at depths of 1.8m in the San Juan Basin. 16 Since pits were about 1 to 1.5 meters deep, the total depth was up to 3.3 meters from ground level. Groundwater in flood plains of New Mexico valleys may be found at 2 meters in depth and contamination of groundwater by hydrocarbons from unlined earthen waste pits was thus predicted as likely, despite mechanisms for attentuation.…”
Section: Hydrocarbons and Aromatic Hydrocarbons In Groundwater Surroumentioning
confidence: 99%
See 1 more Smart Citation
“…Die Tiefenverlagerung polyzyklischer aromatischer Kohlenwasserstoffe (PAK) aus der ungesättigten Zone kontaminierter Standorte leistet einen wichtigen Beitrag zur Grundwasserbelastung (EICEMAN et al 1986). Transportzeiten und -distanzen werden durch PAK-Freisetzung und -Festlegung gesteuert.…”
Section: Introductionunclassified